Tuesday

September 23, 2014

September 23, 2014

Posted by **drwls** on Wednesday, January 17, 2007 at 7:52pm.

Multiply both sides by (4-x)(x+1)

24(4-x) + 12(x+1) = 14(4-x)(x+1)

96 - 12x + 12 = -14(x^2 -3x -4)

= -14x^2 +42 x +56

Combine terms and solve for x.

sorry guys, here's another.I'm not the greatest at math but i do know some...

The rectangle given has a perimeter of 14 units. Find the value(s) of x by factoring a quadriatic equation.

one side= 12/(x+1)

other side= 6/(4-x)

thanks for your help.

**Answer this Question**

**Related Questions**

math - how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 ...

math - The rectangle given has a perimeter of 14 units. Find the value(s) of x ...

algebra - solve the following equation by clearing fractions show all work want ...

MATH - explain how to put 7y-14x=21 in slope intercept form. You want y=mx + b ...

algebra - solve the following equation by clearing fraction want to know if this...

Algebra - Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r...

math - which equation is equivalent to 5x-2(7x+1)=14x? why? a -9x-2=14x b -9xt1=...

Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...

Pre-Algebra - inequality 0.75x>3 Multiply both sides of the inequality by 4/3...

Math - Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + ...